The Effect of Budgetary Slack, Information Asymetry, and Trust on Managerial Decision-Making - Listyarini, Rakhmawati (International Journal of Business, Law, and Education, 2025)
This study investigates the effect of budgetary slack, information asymmetry, and trust on managerial decision-making quality within organizational budgeting contexts. Using a quantitative approach and data collected from 150 managerial respondents across various industries in Indonesia, this research employs Partial Least Squares Structural Equation Modeling (SmartPLS 4.0) to analyze both direct and moderating relationships among the variables. The results reveal that budgetary slack and information asymmetry have significant negative effects on managerial decision-making quality, whereas trust exerts a positive influence. Furthermore, trust moderates the relationships between budgetary slack and information asymmetry with managerial decision-making, such that the negative effects of both variables are weaker under high-trust conditions. These findings highlight the crucial role of trust as a behavioral control mechanism that enhances decision-making quality by fostering transparency and reducing opportunistic behavior. The study contributes to the behavioral management accounting literature by integrating agency theory and social exchange theory to explain how relational factors interact with formal control mechanisms. Practically, organizations are encouraged to reduce information asymmetry and budgetary slack through participative budgeting, transparent communication, and trust-building initiatives, ensuring that managerial decision-making aligns with organizational objectives.